Fractals for an ethnography of time and addiction: Recursive and self-similar temporalities in heroin and poly-substance use - Roe, Laura; Dobroski, Sonja; Manley, Gabriela; Warner, Holly; Dritschel, Heidi; Baldacchino, Alexander Mario (Frontiers in Psychiatry, 2023)
Drawing on both mathematical and anthropological understandings of fractality, this paper explores alternative perspectives of time as it relates to heroin addiction and polysubstance use in Scotland. The paper ethnographically illustrates temporalities which confound typical conceptualisations of linearity, and which can be better understood as fractal. Senses of linear time are disrupted for people who use heroin through intensive poly-substance use, an increasing trend in Scotland, as both time and memory become fragmented beyond coherence or re-assemblage. Distortedness and complexity being common descriptors applied to mathematical fractals, time shattered into uncountable and un-interpretable fragments similarly connotes fracture, dissonance and distortion. A meaningful engagement with fractal theory contains the potential to open up new vocabulary, imagery, and theoretical avenues with which to grasp complex and non-linear time experience. The aims of the paper are, therefore, twofold; to both provide a nuanced ethnographic exploration of substance use time, and to develop a reflexive analytical framework for temporal experience through fractals.